Influence of the physical-mechanical properties in the establishment of the coincidence frequency in the sound isolation of masonry walls - Paixão, Dinara Xavier da (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The article shows the influence of physical-mechanical properties (density, modulus of elasticity, and coefficient of Poisson) in the identification of the coincidence critical frequency in the study of the sound isolation of a ceramic solid brick masonry wall. A data-base of parameters determined in laboratory and obtained in the literature was created for carrying out computational simulation using a software that employs Energy Statistical Analysis. The computational simulation and experimental results were compared, based on the ISO 140 standard. The most influential parameter is the density, both for the analysis of masonry as an isotropic or orthotropic material. .